Pertimbangan Perencanaan Tata Ruang Wilayah Berbasis Yurisdiksi di Kabupaten Kapuas Hulu - Mujio; Rusdiana, Omo; Pribadi, Didit Okta; Shiddiq, Diar; Ermyanyla, Mia; Febriani, Yusi (http://arl-faperta.ipb.ac.id/, 2025)
Kapuas Hulu District is the upstream region of West Kalimantan Province, one of the districts with most of the area being a protected area, or 76% being a forest area (National Park, Protected Forest, and Production Forest). Obviously, the approach to spatial planning in Kapuas Hulu District is different from other regions that have smaller protected areas. Sustainable production is the basis for spatial utilization in Kapuas Hulu District. A jurisdictional approach to sustainable production areas is a suitable concept, as it holistically considers the economic, ecological, and social context within a landscape. Sustainable production areas are designed to simultaneously conserve important ecosystems, establish sustainable agricultural production, and improve the living conditions of local residents. The objective of this research is strategic recommendations and implementation of increased consideration of sustainability aspects in the spatial plan review process. The method used in this study involves a mixed approach that combines qualitative and quantitative methods to obtain comprehensive results. The analysis used is the Interpretative Structural Modeling (ISM) technique. The results of this study are strategic directions for spatial utilization based on the principles, criteria, and indicators of spatial planning, making it easier to carry out monitoring and evaluation and to ensure that the principles of sustainability are implemented.